Computing Education, Decent Work and Economic Growth in Nigeria - Omeh Christian Basil; Ebele Nwokoye; Ebikabowei Biedomo (Yayasan Riset dan Pengembangan Intelektual, 2021)
The Sustainable Development Goal (SDG) 8 is to promote decent work and economic growth. The goal puts at the forefront, workers well-being through employment and decent work that respect the dignity of workers. Countries work towards achieving employment and decent work for inclusive poverty-reducing growth target by 2030. Computing education plays a significant role in achieving the target. This study, therefore, examined the impact of computing education and decent work on economic growth in Nigeria, using Enugu state as a case study. 250 respondents were randomly selected using a structured questionnaire. The Ordinary Least Square (OLS) technique was employed in analyzing the data. Computing education is measured by household investment (enrolment) in ICT/computing education courses. Employment opportunities – employed household members-to-household size, remunerative employment, conditions of work and social security are used to measure decent work. Economic growth, on the other hand, is measured by per capita household income. The results of the study showed that computing education had a significant impact on economic growth. Employment opportunities and social security were also found to had a significant impact on economic growth. Conditions of work had a positive and insignificant impact on economic growth, while remunerative employment had a negative and insignificant impact on economic growth. Computing education and employment opportunities were complementary. Also, there was a complementary effect of computing education and remunerative employment, computing education and decent work, and computing education and social security on economic growth. Among the measures of decent work, conditions of work and social security were complimentary, while employment opportunities and remunerative employment, remunerative employment and conditions of work, and remunerative employment and social security were substitutes. Other variables such as the stock of human and physical capital played some diverse roles in enhancing economic growth. We, therefore, recommend the adoption of supportive policies to encourage computing education and decent work as well as physical and human capital development. In particular, policies to encourage computing education should include the incorporation of compulsory ICT/computing education courses in the nations one-year National Youth Service Corp (NYSC) scheme.